2009
DOI: 10.1161/circulationaha.108.827626
|View full text |Cite
|
Sign up to set email alerts
|

Syncope While Driving

Abstract: Background The risk of syncope occurring while driving has obvious implications for personal and public safety. We aimed to define the clinical characteristics, causes, and prognosis of syncope while driving. Methods and Results In this case-control study of consecutive patients evaluated for syncope from 1996 through 1998 at an academic medical center, we documented causes, clinical characteristics, and recurrence of syncope while driving. Of 3,877 patients identified, 381 (9.8%) had syncope while driving (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Sorajja et al reported that among subjects evaluated for syncope from 1996 to 1998 at Mayo Clinic, 9.8% had at least one syncopal episode while driving. 4 For pilots in high performance aircraft, the high gravity force during training/duty pools blood to the lower body resulting in cerebral hypoperfusion and hypoxia, which may lead to syncope. According to Carter et al, up to 48% of the United State Air Force population has experienced syncope.…”
Section: Introductionmentioning
confidence: 99%
“…Sorajja et al reported that among subjects evaluated for syncope from 1996 to 1998 at Mayo Clinic, 9.8% had at least one syncopal episode while driving. 4 For pilots in high performance aircraft, the high gravity force during training/duty pools blood to the lower body resulting in cerebral hypoperfusion and hypoxia, which may lead to syncope. According to Carter et al, up to 48% of the United State Air Force population has experienced syncope.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of syncope, the late recurrences of syncope (during Ͼ6 months of follow-up), and the overall low incidence of recurrent syncope while driving provide useful information to supplement current recommendations on driving for these patients. 4 Summary: Brugada syndrome is characterized by ST-segment elevation in the right precordial leads and an increased risk of sudden cardiac death. Fundamental questions remain on the best strategy for assessing the real disease-associated arrhythmic risk, especially in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…For occupational drivers, we used the value of 0.02 that was set in the study of the Canadian Cardiovascular Society as the estimated maximal probability that sudden death by syncope results in a fatal or injuryproducing accident [16][17][18][19][20]. While it was difficult to find any associated data that directly provided the Ac for PWE, disease-specific risks for fatal crashes associated with seizures and other medical conditions were compared in a previous study in the United States [21].…”
Section: Estimation Of the Risk Of Fatal Traffic Accidentmentioning
confidence: 99%